Visualización de datos: caminos de ida y vuelta entre arte y ciencia en la producción y consumo de imágenes - Dr. Roberto THERÓN SÁNCHEZ (Fonseca, Journal of Communication, 2023)
Since its origins, data analysis has turned to visual representation to find and offer explanations. Storage and processing capacities are steadily growing thanks to the advancement of computing. At the same time, thanks to technological democratization, artistic contributions in data visualization have multiplied, providing new creative forms and different approaches from those of science.